AGRO-TOURISM ENTREPRENEURSHIP DEVELOPMENT MODEL IN NAMANGAN REGION - MUSAKHANOV, KAZIKHAN (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
The processes of modern changes in the countryside led to the opposite of the expected result - the deterioration of the working conditions and quality of life of the rural population. The difficult economic situation of many rural families has forced them to look for new types of entrepreneurial activities in rural areas, which will create new jobs and thus provide rural residents with an opportunity to earn additional income. Although the main type of business activity in the village is the cultivation of agricultural products and development, the development of rural tourism is an important direction for the implementation of such a strategy.Methods.Terminological analysis, factor analysis, comparative analysis, correlation-regression analysis, expert evaluation, static, economic-mathematical methods were used in the research process.